Connections Between Culinary Tourism Experiences and Memory. (May 2022) - Stone, Matthew J.; Migacz, Steven; Sthapit, Erose
Tourism researchers have identified many factors leading to memorable food tourism (culinary tourism) experiences. This research proposes reasons why food experiences while traveling are especially memorable and proposes avenues for future research on food and memory. The act of travel in addition to the act of eating/drinking and individual attitudes and emotions likely work together to create memories. Travelers agreed with many reasons why food travel experiences are connected with memory. These include sensory connections, emotional connections, social and interpersonal connections, novelty and experimental connections, focus and attention, and reflective connections. These connections may also relate to pretrip expectations. Travelers who identified themselves as motivated to travel for food and drink felt more strongly than other travelers about the reasons that food and drink travel experiences were connected with memory. Suggestions are included for researchers to advance understanding of memorable food tourism experiences.